Probiotics and Biotechnology Advances in Reducing and Preventing Colorectal Cancer; Minireview - Bajes, Hana; Al-Dujaili, Emad (Jordan Journal of Pharmaceutical Sciences, 2019)
Background: Probiotics have been consumed to add health benefits to the human body, however, with aid of biotechnology, probiotics have been used specifically to prevent or reduce cancer. Colorectal cancer can be caused by different factors; primarily the imbalance of normal flora in the intestines. Intake can by fermented food, supplements, or as a carrier to an anti-cancerous agent.Aim and objectives: The intent of this review is to provide relevant information on the effect of probiotics on colorectal cancer and the different mechanism of actions. Some probiotics have been demonstrated; some downregulated inflammation, inhibited the expression of certain markers, or interacted with chemical pathways that lead to apoptosis. Methodlogy: Relevant data were extracted and evaluated, and this was made possible by searching different search engines primarily PubMed and Science Direct using relevant keywords. Collection of literature lasted for about four months. Results: Some societies have been observed for their low prevalence of colorectal cancer which was associated with their rich probiotics diet. Currently, Food industry is racing toward the innovation of new products that can be enriched with viable probiotics and constant research is aimed toward finding effective methods to target colorectal tumor and reduce or inhibit its proliferation.